2019
DOI: 10.3390/su11143805
|View full text |Cite
|
Sign up to set email alerts
|

Family Management and Firm Performance in Family SMEs: The Mediating Roles of Management Control Systems and Technological Innovation

Abstract: The aim of this research is to analyze the mediating role of the use of management control systems (MCS) and the achievement of technological innovation (TI) in the relationship between family management and firm performance in family small and medium-sized enterprises (SMEs). A questionnaire was conducted by 617 managers of family SMEs in Spain, and our model was tested using partial least squares. Our findings show that both MCS and TI play crucial mediating roles in the understanding of the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 139 publications
1
19
0
Order By: Relevance
“…On the other hand, the results reveal that process innovations exert a positive and significant impact on sustainable economic performance. This finding is also in line with prior research [53,111] arguing that process innovations are crucial for the improvement of firms' internal efficiency, flexibility, and quality, leading to important savings in production costs and, thus, to increases in firms' operating results and long-term performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the results reveal that process innovations exert a positive and significant impact on sustainable economic performance. This finding is also in line with prior research [53,111] arguing that process innovations are crucial for the improvement of firms' internal efficiency, flexibility, and quality, leading to important savings in production costs and, thus, to increases in firms' operating results and long-term performance.…”
Section: Discussionsupporting
confidence: 90%
“…[28,51]. In this respect, prior studies have revealed a clearer direct positive effect of innovation outputs on performance indicators than that displayed in the case of innovation inputs [32,52,53].…”
Section: Innovation Inputsmentioning
confidence: 83%
“…Performance was evaluated with a scale of three items based on previous research [4,78,79]. The scale created has been used to measure the financial and non-financial performance of companies, in aspects such as profitability, sales growth, and customer satisfaction, in comparison with the performance of their competitors.…”
Section: Performancementioning
confidence: 99%
“…MSMEs are reactive, flexible and risky organizations, but they are more innovative than bigger companies (Ruiz-Palomo et al, 2019). Innovation is always correlated with decisionmaking out of unexpected opportunities, exceptions, new relations and uncertainty of result, and it is at high risk of failure (Davila et al, 2009).…”
Section: Innovation-performance Relationshipmentioning
confidence: 99%